Design for Aging : International Case Studies of Building and Program. - Anderzhon, Jeffrey W. (Wiley series in healthcare and senior living design., 2012)
Architecture/Interior DesignAn in-depth look at the most innovative aged care facilities todayWith the world's population aging at a rapid pace, there is a growing need for new ways to provide residential care for older people. Design for Aging explores some of the most successful examples of elderly housing today, focusing on integrating architectural considerations within an unwavering people-driven approach. Written by an international team of experts in aged care design, the book brings together twenty-six case studies from around the world, including Australia, Denmark, England, Japan, th.